A major plant practice at the Rookie Fruit Preserves, Km 12 Catalunan Pequeño, Davao City - Gonzaga, Larie Lyn Caligan (2007)
As a part of the curriculum for the Bachelor of Science in Food Technology, a plant practice was conducted at Rookies Fruit Reserves for 288 hours to apply the principles learned by the student in the academe to the actual food processing plant. During the plant practice the student was directly involved in the processing operations of the company, from receiving of raw materials to dispatching of finished products. After the practicum, the student was able to gather information about the company?s profile, Good Manufacturing Practices (GMPs) standards, and develop interpersonal relation skills with other plant personnel. Moreover, problems related to processing were identified and recommendations were presented for plant improvement. The plant practice gave the student an outlook on the significance and roles of food technologists in the food industry
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2007
Keywords: Fruits; Fruits -- Processing